PENGARUH PENGGUNAAN TEPUNG DAUN BINAHONG (Andredera cordifolia) (Ten) (Stennis) SEBAGAI Feed Additive TERHADAP KUALITAS KARKAS AYAM PEDAGING - Muiz, Abdul (AgriSains, 2016)
The binahong leaves (Andredera cordifolia (Ten) Stennis) contains phytochemical compounds that have the potentialas feed additive. Itused as a supplementary ration that canimprovecarcassqualityofbroilers. The research aimed to study benefit of the binahong leaves powder as a feed additive towards carcass quality ofbroilers. This research was conductedin the farm of Faculty ofAnimal Husbandryand Fishery, Tadulako University, Palu. The used material of this study were 80 DOCbroiler chickens and were placed in an individual cage with a size of 100x 100 x 60 cm. The completely randomized design was applied with4 treatmentsand5replications.The tested treatments were 4 levels of binahong leaf powder mixed into the ration: R0 (ration without leaf powder binahong); R1 (ration with leaf powder binahong 0.5%); R2 (ration with leaf powder binahong 1%); and R3 (raation with leaf powder binahong 1,5%); The results ofvariance analysis showedthat theuse ofleaf powderbinahongasadditivein the ration had significant effect (P<0,05) to percentage of carcass, percentage of chestcarcass component, as well as Â percentage of abdominal fat.The average percentage ofcarcassfor the treatmentR0(67,3%), R1 (68,3%), R2 (69,0%) and R3 (69,9%). The average percentage of chest carcass component for the treatment R0 (34,1%), R1 (34,5%), R2 (35,1%) and R3 (35,6%). The average percentage of abdominal fat for thetreatmentR0 (1,49%), R1 (1,46%), R2 (1,13%) and R3 (1,07%). It can be concludedthat theuse ofbinahongleaf powderup1.5% levelasfeedadditivein the rationresulted inthe best resultsonthe physicalquality ofbroilercarcasses.Keywords: abdominal fat,broiler, carcass, leafbinahong powder.